Analysis of Student's Difficulty in Solving Mathematical Problems in Linear Programs - Fitrieyah, Imamah Dien; Mabrouk, Anouar Ben (Journal of Teaching and Learning Mathematics, 2024)
This research aims to analyze students' difficulties in solving mathematical problems on linear programming material using qualitative descriptive methods based on the Polya heuristic. This research involved students with high, medium, and low abilities through analysis of written tests and student interviews. Data was collected from 30 class XI students at SMA X using specially designed written tests and in-depth interviews. Data analysis was carried out using thematic analysis techniques. The research results show that students with high abilities do not experience difficulties in working on contextual problems in linear programming material. Students with moderate abilities experience difficulty in determining the sign of inequality and the set of solution areas. Meanwhile, students with low abilities experience difficulties in various aspects, including understanding basic concepts and applying problem-solving steps. Specific examples of difficulties experienced include errors in drawing graphs and determining intersection points. As a recommendation, teachers are advised to introduce and explain problem-solving according to Polya's heuristics more concretely and systematically. For example, using Polya steps in varied practice sessions and providing specific feedback at each stage of problem-solving. In this way, students' understanding of linear programming material can be significantly improved.